ANALISIS GEN TCF7L2 (Trancription Factor 7 Like 2) PADA KELUARGA PENDERITA DIABETES MELLITUS TIPE 2 KECAMATAN TANGGULANGIN, KABUPATEN SIDOARJO - Miftahul Mushlih; Siti Asriani Iknan; Hindah Sabrina Amin; Siti Cholifah; Bayu Segara (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
Diabetes mellitus is a metabolic disorder characterized by not produced insulin or disruption of insulin action. Diabetes mellitus was reported correlated with TCF7L2 gene mutation. This study aimed to analyze the TCF7L2 gene in families with type 2 diabetes. 5 samples were used in this study, the methods flow through DNA Isolation, PCR, and sequencing. Samples were amplified by the PCR technique using primers that were designed to detect the TCF7L2 gene, (F: 5'-GGCTTGATTGTTGATTATGGGC3' and R:5 'TCTGGCACTCAGAGAGT 3'). The amplification and sequencing resulted in 368 bp (located at 103631-103972 bp). We found a transition mutation at C103950T. The polymorphisms found may characteristic in this population because they are not found in other sequences. Keywords : Diabetes mellitus, TCF7L2 gene, mutation